2021
DOI: 10.3390/app112411759
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Profile Assessed by Bioimpedance and Anthropometry Measures of Male and Female Rugby Players Competing in the Spanish National League

Abstract: Different rugby positions make different demands on players. It therefore follows that optimum body composition may vary according to the position played. Using anthropometry and bioimpedance analysis (BIA) to assess body composition, the present study aimed to compare the effect of sex and position on body composition variables using anthropometry and BIA methods. A total of 100 competitive rugby players (35 women and 65 men) competing in the First Spanish National League were recruited voluntarily and for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Two studies reported anthropometric measures by DXA alone (16,60), with 3 studies reporting measures via skinfold (20,22,58), and one study reporting measures by ADP (36). The remaining studies used a combination of DXA and skinfolds (39) and skinfolds and BIA (41), respectively. Anthropometric and body composition metrics are presented in Table 4.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two studies reported anthropometric measures by DXA alone (16,60), with 3 studies reporting measures via skinfold (20,22,58), and one study reporting measures by ADP (36). The remaining studies used a combination of DXA and skinfolds (39) and skinfolds and BIA (41), respectively. Anthropometric and body composition metrics are presented in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…‖Mean sum of skinfolds calculated by authors from 5 year skinfold site data within Woodhouse et al (58). {Data presented are mean of both methods adopted within Ramos-Alvarez et al (41). Sum of total sites presented in bold are those adopted within relevant studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations